A novel sensitive visual count card for detection of hygiene bio-indicator—molds and yeasts in contaminated food. (January 2020) - Xu, Linlin; Chen, Ping; Liu, Tong; Ren, Dayong; Dong, Na; Cui, Wenwen; He, Pai; Bi, Yunfeng; Lv, Na; Ntakatsane, Moeketsi
Abstract: The study developed a novel, sensitive and visual count card for detection of molds and yeasts in food. A series of concentrations of ethanol and four cations for molds and yeasts growth and coloration were evaluated. Furthermore, cold water gel texture of count card was also determined under the conditions. These results demonstrated that the effects of 8 mL L −1 ethanol, 0.2 g L −1 CuSO4, 0.2 g L −1 CaCl2 and 0.1 g L −1 ZnCl2 promoted the growth and coloration of molds and yeasts, especially inhibited fungal hyphae spreading to eliminate the omissions by mutual hyphae coverage. The gels texture was satisfactory for molds and yeasts growth. Two kinds of non-diffused chromogenic agents in different concentrations for molds and yeasts were also evaluated. The compound chromogenic agents (5-bromo-4-chloro-3-indolyl phosphate and nitrophenyl palmitate) provided more sensitive and accurate count card for detection of molds and yeasts. Artificial contamination method was used to evaluate the performance of detecting count card of molds and yeasts. Compared with national standard agar plate method (for 5–7 days), the count card (for 36 h) reduced detection time greatly. Highlights: A novel visual count card was developed for detection of molds and yeasts in food. Modified textural properties of gels promoted optimal growth and count of molds and yeasts. Non-diffused chromogenic agents improved the count card sensitivity and accuracy.